Inovasi Pendidikan sebagai Solusi Permasalahan Pendidikan - Nia Nur Afni Fitria; Alvira Fedora; Kholifatun Khasanah; Rizka Elan Fadilah; I Ketut Mahardika; Firdha Yusmar (FKIP e-PROCEEDING, 2022)
Educational innovation itself is a new change that is sought to improve learning in order to achieve goals in education, educational innovation is sought as a reference for a better education movement. With educational innovation, it is hoped that it will be able to solve educational problems and realize quality education in the future. This paper aims to describe educational innovation as a solution to education problems and Indonesia's readiness to solve educational problems. In Indonesia, readiness to face educational challenges is carried out by increasing the knowledge and skills of human resources through educational innovation. Education management policies in Indonesia currently encourage all levels of education, especially higher education, to take advantage of advances in digital technology in the modern era. In today's digital era, technology can be used as a driving factor for the success of educational innovation with the presence of sophisticated technology that can encourage the achievement of educational reform goals. In addition to the use of technology in the modern era, it is necessary to innovate learning methods that can make it easier for students to understand learning materials, so as to improve the quality of education in Indonesia!